Australia’s Travel Advice Policy and Its Impact on Australian Tourist Visits to Bali - Putu Ratih Kumala Dewi (Universitas Udayana, 2021)
The plan to ratify the new Criminal Code in Indonesia is responded by Australia through issuing a travel advice policy in 2019. There has a concern that this policy will have an impact on the tourism sector in Indonesia, especially Bali, because the Australian tourists are recorded as dominating the visits. By using the concept of travel advice and foreign policy, this study aimed to analyze the travel advice policy issued by Australia from the perspective of International Relations and its impact on the tourism in Bali. This study used qualitative descriptive method and the primary data collection was done through interviews with the hoteliers in Bali and Australian tourists visiting Bali. From the perspective of International Relations, it is found that Australia’s travel advice is a foreign policy that has a purpose based on Australia’s national interests. This policy has no impact on Australian tourist visits because it is not a binding policy. The Australian tourists' have their own opinion about Bali and the decisions to visit affected by the clarity information from targeted state or destination.